Using Knowledge to Facilitate Pinpointing of Factoid Answers - Hovy, E.H.; Hermjakob, U.; Lin, Chin-Yew; Ravichandran, Deepak (19th International Conference on Computational Linguistics (COLING 2002), 2002)
In order to answer factoid questions, the Webclopedia QA system employs a range of knowledge resources. These include a QA Typology with answer patterns, WordNet, information about typical numerical answer ranges, and semantic relations identified by a robust parser, to filter out likely-looking but wrong candidate answers. This paper describes the knowledge resources and their impact on system performance.